2019
DOI: 10.1038/s41598-019-54369-7
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic score vs blood cell indices for determining timing of immunomodulator withdrawal in quiescent ulcerative colitis

Abstract: While immunomodulators (IMs) are used as key drugs in remission maintenance treatment for ulcerative colitis (UC), there has been no evidence to date for determining monitoring methods and drug withdrawal. Therefore, we examined if a decrease in white blood cell count (WBC) and an elevation in mean cell volume (MCV) could be used as optimization indices and if mucosal healing (MH) could be a rationale for determining the time of IM withdrawal. Subjects were 89 UC patients who were using IMs and for whom clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Similarly, Cassinotti et al conducted a long-term survey in 155 patients with UC who discontinued AZA during the remission period and found relapse in one-third of patients after 1 year and in half of the patients after 2 years (Cassinotti et al, 2009). We have also previously demonstrated that the relapse rate is greater in the withdrawal group when comparing remission maintenance rates between thiopurine continuation and withdrawal groups of patients with UC with long-term sustained remission, and showed that endoscopic remission (Mayo endoscopic subscore 0) did not guarantee the absence of relapse after withdrawal (Takenaka et al, 2019). As described, a high relapse risk clearly exists with the withdrawal of thiopurines administered as remission maintenance therapy.…”
Section: Involvement Of Long-term Thiopurines and Onset Of Lymphoproliferative Disorders (Lpds)mentioning
confidence: 91%
“…Similarly, Cassinotti et al conducted a long-term survey in 155 patients with UC who discontinued AZA during the remission period and found relapse in one-third of patients after 1 year and in half of the patients after 2 years (Cassinotti et al, 2009). We have also previously demonstrated that the relapse rate is greater in the withdrawal group when comparing remission maintenance rates between thiopurine continuation and withdrawal groups of patients with UC with long-term sustained remission, and showed that endoscopic remission (Mayo endoscopic subscore 0) did not guarantee the absence of relapse after withdrawal (Takenaka et al, 2019). As described, a high relapse risk clearly exists with the withdrawal of thiopurines administered as remission maintenance therapy.…”
Section: Involvement Of Long-term Thiopurines and Onset Of Lymphoproliferative Disorders (Lpds)mentioning
confidence: 91%
“…Consistent with previous publications, we found statistically significant differences in faecal calprotectin concentrations according to endoscopic activity. We also examined other serum biomarkers to assess endoscopic activity in CED, but only CRP showed statistical significance, whereas other biomarkers were inappropriate for endoscopic activity [ 19 ]. CRP was used before to distinguish between quiescent and active disease, but in general, the correlation between CRP and endoscopic activity is lower than that between faecal markers and activity [ 12 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, all studies on the endoscopic severity of patients with UC have assigned a single MES score to a single endoscopic image. However, MES may often vary depending on the location in a single picture (Fig 3A -3C), especially in the resolution phase [7][8][9][32][33][34][35][36]. In addition, systematic disease severity along the length of the colorectum has been elusive because images are taken at undefined intervals during colonoscopy.…”
Section: Plos Onementioning
confidence: 99%